PENGARUH KOMUNIKASI INTERPERSONAL, KOMPENSASI KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA GURU [THE EFFECT OF INTERPERSONAL COMMUNICATION, JOB COMPENSATION, AND JOB MOTIVATION ON TEACHER PERFORMANCE] - Maria Arika Purwaningratri (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
Teacher performance is one of the most important things that shows that the learning process is running well. The learning process is the way to achieve the learning goals and foundation’s goals. Teacher performance can be affected by several things, such as interpersonal communication, job compensation, and job motivation. Therefore, this research is going to find out the impact of interpersonal communication, job compensation, job motivation towards teachers’ performances. This research used the quantitative approach and path analysis method. The subjects of this research were 30 teachers of SDS Saint Peter Kelapa Gading. The data were collected from 4 March 2016 until 11 March 2016. The data were processed by the SmartPLS software to try out the research instrument and hypothesis. Based on the data processing, there are five findings show that (1) interpersonal communication has a positive impact in teachers performances, (2) job compensation has a positive impact on teachers performances, (3) interpersonal communication has a positive impact on job motivation, (4) compensation has a positive impact on job motivation, (5) job motivation has a positive impact on teachers performances. In this research, interpersonal communication is strongly influenced toward the teachers’ performances.